2015
DOI: 10.3851/imp3044
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antiviral Drug Synergy in an Infectious HCV System

Abstract: Background Direct-acting antivirals (DAAs) have greatly improved the treatment of HCV infection. To improve response and prevent resistance, combination regimens have been the focus of clinical development. Regimens are often first assessed in vitro, with most combination studies to date using subgenomic replicon systems, which do not replicate the complete HCV life cycle and preclude study of entry and assembly inhibitors. Infectious full-length HCV systems have been developed and are being used to test drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…This is particularly important against viruses which keep evolving continuously due to higher rate of mutation. The benefit of treatment strategies involving synergism has been already reported in case of HIV and HCV infections 47,48 . These inhibitors may lead to one therapeutic solution against the diversity of DV serotypes by efficiently targeting and inhibiting the catalytic function of three functionally conserved non-structural proteins.…”
Section: Discussionmentioning
confidence: 93%
“…This is particularly important against viruses which keep evolving continuously due to higher rate of mutation. The benefit of treatment strategies involving synergism has been already reported in case of HIV and HCV infections 47,48 . These inhibitors may lead to one therapeutic solution against the diversity of DV serotypes by efficiently targeting and inhibiting the catalytic function of three functionally conserved non-structural proteins.…”
Section: Discussionmentioning
confidence: 93%
“…This is critically important against constantly evolving CoVs. The benefits of treatment strategies involving pan-inhibitors have already been reported in the case of Dengue virus [ 28 , 117 ], HCV [ [118] , [119] , [120] , [121] ], and HIV [ 122 ]. The screened inhibitors in the present study may lead towards a medicinal solution against the variety of constantly evolving CoVs by effectively targeting/hindering the proteolytic role of their PL pro .…”
Section: Resultsmentioning
confidence: 99%
“…Advancements in HCV cell culture systems allowed us to approach this problem from a phenotypic perspective, to develop treatments that have a different mode of action from the existing DAAs, and are thus likely synergistic with currently available drugs due to their mechanism of action [21][22][23]. We have previously shown that CCZ inhibits the entry step of HCV infection and exhibits synergistic activity with currently approved anti-HCV agents in vitro [14,24]. The mechanism of action of CCZ and related compounds has been proposed to target the fusion process of viral entry, possibly involving the fusion loop sequence of the HCV E1 protein [25].…”
Section: Discussionmentioning
confidence: 99%